Análise espacial da criminalidade nos municípios paraibanos entre os anos de 2011 e 2013 - Anjos Júnior, Otoniel Rodrigues dos (2015)
The overall objective of this dissertation is to analyze the determinants of crime in cities in Paraíba between the years 2011 and 2013. This analysis is based on the theoretical work of Becker (1968). Therefore, it is considered the agent as optimizer of its shares and, therefore, can make rational decisions between crime and no crime throughout life. Crime data were provided by the Department of Security and Social Defense of Paraíba State, while the rest were from the IBGE Census (2010). Initially, we note that in the last decade crime rates that have affected the state of Paraiba were materially higher than those observed in the Northeast and Brazil. It is found based on descriptive statistics data that criminals follow certain pattern of action with respect to the day of the event, and more shift used in arms offenses. In addition, the data were able to demonstrate characteristics of victims, for example, the age and gender most affected. The results were sufficient to identify ten concentrations crimes in state between the years 2011 and 2013. Note , for example, crime is concentrated in a group of cities that are repeated throughout the years , however , They show changes in order that they appear. He built up an analysis of the penitentiary system in recent years Paraiba , considering , therefore, jail time and the age of convicts . Finally, the spatial analysis of the data was performed . It performed the Exploratory Analysis of Spatial Data ( ESDA ) in order to describe and visualize spatial distributions through the Global Moran statistics and Local ( LISA) . Such procedure aims to test the existence of spatial dependence in the average rate of crime that affects the cities in Paraíba between 2011 and 2013. The results of the estimated models suggest the presence of spatial dependence in the data. Thus, this result makes it impossible to use the MCRL . So he went to the estimation of global spatial models : SAR , SEM and SAC . However , statistical considerations suggest that the best form of treatment is found spatial dependence on SAR specification. In this context , it was noted that all the independent variables used in the model ( degree of urbanization , urban population density , religious density , GDP density , concentration index of Gini income and HDI ) proved significant in explaining the problem of crime Paraiba recent years.